Many-body out-of-equilibrium dynamics of hard-core lattice bosons with non-local loss - Everest, Ben; Hush, M.R.; Lesanovsky, Igor (American Physical Society, 2014)
We explore the dynamics of hard-core lattice bosons in the presence of strong non-local particle loss. The evolution occurs on two distinct time-scales, first a rapid strongly correlated decay into a highly degenerate Zeno state subspace, followed by a slow almost coherent evolution. We analytically solve the fast initial dynamics of the system, where we specifically focus on an initial Mott insulator state, and perform an analysis of the particle arrangements in the Zeno subspace. We investigate the secondary slow relaxation process that follows and find an intricate regime where the competition between dissipation and coherence results in various types of interacting particle complexes. We classify them and analyse their spectral properties in the presence and absence of nearest-neighbor interactions. Under certain circumstances the dispersion relations of the complexes feature flat bands, which are a result of an effective spin-orbit coupling.